Investigating the Differentiated Instruction of International EFL Teachers in Chinese Bilingual Primary Schools - Mina Liang; Bin Zou (SAGE Open)
In the context of globally integrated education, the last decade has seen a significant rise in bilingual primary schools across China. This development has led to the recruitment of an increasingly diverse group of international teachers to deliver English as a Foreign Language (EFL) education. These EFL teachers introduce a wide array of cultural perspectives, educational beliefs and values into the Chinese EFL teaching environment, transforming these schools into multicultural educational settings primarily through the diversity of the teaching staff rather than the students. This qualitative study explores the development and effectiveness of Differentiated Instruction (DI) in such environments, employing semi-structured interviews of teachers from various cultural backgrounds across three bilingual schools in Mainland China. Based on thematic analysis, the findings highlight that collaborative teaching, standards-based assessments, ongoing professional development, and integrated home-school educational strategies are crucial for the effective implementation of DI.